Kajian Mutu Air Laut Dan Lingkungan Kawasan Pesisir Kabupaten Bangka Selatan - M. Rizza Muftiadi; Siti Aisyah; Arthur Farhaby; Andi Gustomi; Okto Supratman; Okto Supratman (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
The purpose of this study is to determine the water quality analysis in South Bangka Regency, especially the coastal area, by analyzing the physical-chemical conditions and suitability of salt pond locations. The location of study was conducted in the coastal area of Mempunai, Batu Perahu, Kubu, Tanjung Kemirai, and Puding. The location of study was conducted in the coastal area of Mempunai, Batu Perahu, Kubu, Tanjung Kemirai, and Puding. During the present investigation the minimun and maximum value of water temperature (29 – 32oC), brightness (0,32 – 0,87 m), current (0 – 0,35 m/s), tidal are commonly diurnal (one high and one low tide each day), pH (6,7 – 8,2), salinity (30 – 33,2 o/oo) These areas are dominated by sand and clay. The result of salt pond location suitability analysis is based on water quality in the coastal area. Mempunai, Kubu, Tanjung Kemirai and Puding Beach generally quite-appropriate for salt pond location, different with coastal area of Batu Perahu have inappropriate category for suitability of salt pond location